2022
DOI: 10.3390/jcm11020345
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Combining Transcranial Direct Current Stimulation and Active Fully Embodied Virtual Reality for Visual Height Intolerance: A Double-Blind Randomized Controlled Study

Abstract: Background: Transcranial Direct Current Stimulation (tDCS) and Virtual Reality Exposure Therapy (VRET) are individually increasingly used in psychiatric research. Objective/Hypothesis: Our study aimed to investigate the feasibility of combining tDCS and VRET with the features of wireless, 360° full immersion and embodiment and an active task to reduce height-induced anxiety. Methods: We carried out a pilot randomized, double-blind, controlled study associating VRET (two 20 min sessions with a 48 h interval, du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Another series of studies investigated whether VRET for acrophobia can be boosted by additional brain stimulation or pharmacological treatment. Regarding brain stimulation, one study (Herrmann et al, 2017) thereby reported an acceleration of VRET effects if the medial prefrontal cortex was stimulated by repetitive transcranial magnetic stimulation before VRET conduction, whereas another study (Bulteau et al, 2022) found no such acceleration effects after transcranial direct current stimulation of the ventromedial prefrontal cortex during VRET conduction. Regarding pharmacological treatment, in turn, some studies found no differences between VRET + pharmacological treatment and VRET + placebo treatment (Meyerbroeker, Morina, & Emmelkamp, 2018; Tart et al, 2013), whereas two controlled trials (de Quervain et al, 2011;Ressler et al, 2004) reported greater reduction of acrophobia after VRET + pharmacological treatment.…”
Section: Therapy Studiesmentioning
confidence: 99%
“…Another series of studies investigated whether VRET for acrophobia can be boosted by additional brain stimulation or pharmacological treatment. Regarding brain stimulation, one study (Herrmann et al, 2017) thereby reported an acceleration of VRET effects if the medial prefrontal cortex was stimulated by repetitive transcranial magnetic stimulation before VRET conduction, whereas another study (Bulteau et al, 2022) found no such acceleration effects after transcranial direct current stimulation of the ventromedial prefrontal cortex during VRET conduction. Regarding pharmacological treatment, in turn, some studies found no differences between VRET + pharmacological treatment and VRET + placebo treatment (Meyerbroeker, Morina, & Emmelkamp, 2018; Tart et al, 2013), whereas two controlled trials (de Quervain et al, 2011;Ressler et al, 2004) reported greater reduction of acrophobia after VRET + pharmacological treatment.…”
Section: Therapy Studiesmentioning
confidence: 99%
“…Dcycloserine, a partial NMDA receptor antagonist with effects on fear conditioning, shows mixed results when used during exposure sessions; the number and timing of doses may moderate response (Hofmann, 2014;Mataix-Cols et al, 2017;Norberg et al, 2008) but targeted, pre-registered tests of proposed moderators failed to demonstrate an augmenting effect (e.g., Smits et al, 2020). Transcranial magnetic stimulation (TMS) or transcranial direct current stimulation (tDCS) to increase or decrease activity in learning-related cortical regions during exposure have not been consistently effective (Bulteau et al, 2022;Cobb et al, 2021;Isserles et al, 2021;Zaizar et al, 2021). Behavioral approaches that normatively enhance extinction, such as novelty-facilitated extinction (Dunsmoor et al, 2015), do not improve exposure therapy outcomes in people with anxiety (Steinman et al, 2022).…”
Section: B What Is Missing From Our Understanding Of Exposure?mentioning
confidence: 99%